2018
DOI: 10.1088/1361-6501/aae408
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement method of pressure and temperature using dual-layer PSP/TSP with lifetime-based method

Abstract: Recently, the application field of pressure measurement technique using pressure sensitive paint (PSP) has been expanding. However, temperature dependence of PSP is one of a serious obstacle to accurate pressure measurement in low gauge pressure condition because PSP is absolute pressure sensor. Therefore, temperature information of PSP is indispensably required for accurate pressure measurement, especially in low gauge pressure condition. As a result, both temperature information and pressure information with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The image acquisition (gate) timings, denoted by t i (j) , where i is the gate number and j is the start and end of the gate, must be selected carefully because they affect pressure and temperature sensitivities and signal-to-noise ratio [35,[41][42][43][44][45]. Sugioka et al [43] suggested the following four criteria to obtain better sensitivity characteristics and a higher signal-tonoise ratio for the two-gate method of PSP.…”
Section: Lifetime-based Methodmentioning
confidence: 99%
“…The image acquisition (gate) timings, denoted by t i (j) , where i is the gate number and j is the start and end of the gate, must be selected carefully because they affect pressure and temperature sensitivities and signal-to-noise ratio [35,[41][42][43][44][45]. Sugioka et al [43] suggested the following four criteria to obtain better sensitivity characteristics and a higher signal-tonoise ratio for the two-gate method of PSP.…”
Section: Lifetime-based Methodmentioning
confidence: 99%
“…For temperature compensation, which is required for accurate pressure measurements, Ru(phen) 3 , whose lifetime is in the order of µs, was added as a temperature indicator to a PSP composed of PtTFPP in poly(TMSP). The luminescence lifetime of the porphyrin is about one order of magnitude larger than that of Ru(phen) 3 , thus, simultaneous measurements can be carried out using lifetime-based methods [237]. PtTFPP in a porous polymer/ceramic binder served also as a PSP for unsteady measurement on a helicopter blade.…”
Section: Dual Paintsmentioning
confidence: 99%
“…However, such sensors acquire pressure information at a single point, which is insufficient for comprehensive study of a flow field. Pressure-sensitive paint (PSP) has received significant attention as a nonintrusive method for surface pressure measurements [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The luminescent intensity of PSP is sensitive to the partial pressure of oxygen in a test gas due to a photophysical process called oxygen quenching [ 15 ].…”
Section: Introductionmentioning
confidence: 99%